Elio [videorecording (DVD)] - Sharafian, Madeline, 1993-; Shi, Domee, 1989-; Molina, Adrian; Cho, Julia; Hammer, Mark (Screenwriter); Jones, Mike, 1971-; Molina, Adrian; Simonsen, Rob, 1978-; Williams, Derek (Cinematographer); Rempel, Jordan (Disney ; Pixar, 2025)
"The cosmic misadventure introduces Elio, a space fanatic with an active imagination and a huge alien obsession. So, when he's beamed up to the Communiverse, an interplanetary organization with representatives from galaxies far and wide, Elio's all in for the epic undertaking. Mistakenly identified as Earth's ambassador to the rest of the universe, Elio must form new bonds with eccentric alien life-forms, navigate a crisis of intergalactic proportions, and somehow discover who and where he is truly meant to be."--